THE EFFECT OF FERMENTATION METHOD, MICROBES INOCULATION AND CARBON SOURCE PROPORTION ON THE QUALITY OF ORGANIC FERTILIZER MADE FROM LIQUID WASTES OF CHICKEN SLAUGHTERHOUSE - Sastro, Y.; Bakrie, B.; Sudolar, N.R. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
This study was to examine the effect of fermentation, inoculation, and the proportion of carbonsources on the quality of organic fertilizer made from fermentation of liquid waste collected fromchicken slaughterhouse in Jakarta area. The parameters being tested included fermentation, microbialinoculation, and carbon source proportion. The observations were made after three weeks offermentation on the color, odor, pH, contents of elements C, NH4, NO3, total-N, P2O5, K2O andpathogenic microbes (Fusarium sp., Coletotrichum sp., Salmonella sp. and Eschercia coli). The fertilizerwere implemented for green chinese cabbage in six locations. It was found that the aerobic fermentationsystem combined with inoculation of the decomposer microbes (Lactobacillus spp.) and the addition20% (v/v) of a carbon source was the most appropriate method of fermentation in the production ofliquid organic fertilizers from liquid waste of chicken slaughterhouse. The quality of the fertilizer whichis based on physical, chemical and biological characteristics and crop responses still less than the similarcommercial fertilizer (EM4). Nevertheless, the nitrogen and phosphor contents of this liquid fertilizer(92,000 ppm and 143,000 ppm) were significantly higher (P<0.05) than the EM4 (0.07 and 3.22 ppm).